The Colletotrichum acutatum Species Complex as a Model System to Study Evolution and Host Specialization in Plant Pathogens - Baroncelli, Riccardo; Talhinhas, Pedro; Pensec, Flora; Sukno, Serenella A.; Le Floch, Gaetan; Thon, Michael R. (Frontiers in Microbiology, 2017)
Colletotrichum spp. infect a wide diversity of hosts, causing plant diseases on many economically important crops worldwide. The genus contains approximately 189 species organized into at least 11 major phylogenetic lineages, also known as species complexes. The Colletotrichum acutatum species complex is a diverse yet relatively closely related group of plant pathogenic fungi within this genus. Within the species complex we find a wide diversity of important traits such as host range and host preference, mode of reproduction and differences in the strategy used to infect their hosts. Research on fungal comparative genomics have attempted to find correlations in these traits and patterns of gene family evolution but such studies typically compare fungi from different genera or even different fungal Orders. The C. acutatum species complex contains most of this diversity within a group of relatively closely related species. This Perspective article presents a review of the current knowledge on C. acutatum phylogeny, biology, and pathology. It also demonstrates the suitability of C. acutatum for the study of gene family evolution on a fine scale to uncover evolutionary events in the genome that are associated with the evolution of phenotypic characters important for host interactions.